2014
DOI: 10.1182/blood-2013-11-512764
|View full text |Cite
|
Sign up to set email alerts
|

Biology of tissue factor pathway inhibitor

Abstract: Recent studies of the anticoagulant activities of the tissue factor (TF) pathway inhibitor (TFPI) isoforms, TFPIα and TFPIβ, have provided new insight into the biochemical and physiological mechanisms that underlie bleeding and clotting disorders. TFPIα and TFPIβ have tissue-specific expression patterns and anticoagulant activities. An alternative splicing event in the 5′ untranslated region allows for translational regulation of TFPIβ expression. TFPIα has 3 Kunitz-type inhibitor domains (K1, K2, K3) and a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
249
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(254 citation statements)
references
References 132 publications
0
249
1
2
Order By: Relevance
“…One potential target for alternative treatment strategies is tissue factor pathway inhibitor (TFPI), the primary inhibitor of the initiation of coagulation. It binds and inhibits factor VIIa (FVIIa) in complex with tissue factor (TF), and factor Xa (FXa), with the overall effect of reduced thrombin generation and decreased blood coagulation [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…One potential target for alternative treatment strategies is tissue factor pathway inhibitor (TFPI), the primary inhibitor of the initiation of coagulation. It binds and inhibits factor VIIa (FVIIa) in complex with tissue factor (TF), and factor Xa (FXa), with the overall effect of reduced thrombin generation and decreased blood coagulation [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Indeed, when the intrinsic tenase pathway leading to factor Xa (FXa) activation is blocked due to FVIII or FIX deficiency, a small amount of FXa can be generated by the extrinsic tenase (FVIIa/tissue factor), but it is immediately neutralized by binding of TFPI through its Kunitz 2 (K2) domain while the Kunitz 1 (K1) domain of TFPI subsequently binds to FVIIa, inhibiting the tenase. 4,5 Our team has postulated an original anti-TFPI strategy, Gla-domainless factor Xa (GD-FXa), deprived of its membrane binding domain, and we have validated the proof of concept of this approach. Indeed, GD-FXa reconstituted thrombin generation in plasmas from hemophiliacs.…”
mentioning
confidence: 99%
“…Eighty-five percent of TFPI circulating in the blood is inactive and connected with lipoproteins, and 15% of TFPI occurs in an active form which rapidly inhibits TF/VIIa complex. 1,4 It has been shown that TFPI infusion suppresses thrombosis, which has been induced in experimental animals by TF or endotoxin. On the other hand, tissue factor pathway inhibitor deficiency leads to the thrombotic process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tissue factor pathway inhibitor deficiency leads to the thrombotic process. [4][5][6] Protein C (PC) is an important component of the inhibition system associated with endothelium. PC activation requires binding to 2 receptors present on the surface of endothelial cells; thrombomodulin and endothelial protein C receptor (EPCR).…”
Section: Introductionmentioning
confidence: 99%